Effects of hypertension on the outcomes of Covid-19 infected patients- A retrospective study - yeasmeen, Sabina; Mondal, Montosh Kumar; Hoque, AKM Faizul; Masud, Sanaul Haque; Sultana, Shofina; Banik, Debabrata (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Hypertension has been reported as the most prevalent comorbidity in patients with corona virusdisease 2019 (COVID-19) .Since hypertension is exceedingly frequent in the elderly and older people appear tobe at particular risk of being infected with SARS-COV-2 virus and of experiencing severe forms andcomplications of COVID-19. Objective : This retrospective study aim to compare the outcomes in COVID-19 infected patients with orwithout hypertension. Method : Atotal 180 hospitalized patients with laboratory confirmed COVID-19 were included. The medicalrecord including clinical feature, history of hypertension were included in this study. This study wasconducted in COVID-19 ICUof Bangabandhu Sheikh Mujib Medical University from August 2020 to January2021.Informationwere obtained frommedical record including clinical features, complication,treatments andclinical outcome were extracted for the analysis. Results: There were 180 patients selected for this study. 50(27.8%) patients had 51-60 years ,79(43.5%)patients had61-70 years and 27(15%) patients had 71-80 years.This study showed that 71.7% patients washypertensive and 29.3% patients was non-hypertensive. In total 180 patients, mortality rate was 65.1% inhypertensive patientsand mortality rate was41.1% in non-hypertensivepatients.Among them patientscomorbidity was 50% Diabetes mellitus,14% Bronchial asthma,14% patients Ischemic heart disease, 11%Chronic Kidney disease ,6% hypothyroidism and 5% cerebrovascular disease. Conclusion: This study concluded that hypertension does not affect the outcome of COVID-19. Compared withthe group of survivors and non-surviving COVID-19 patients with hypertension, most of the patients were olderand had more comorbidity. JBSA 2021; 34 (2) : 44-48